System integrated business process reengineering of an International Air Cargo Hub - Sia, Edwin Geok Lin. (2008)
Information technology plays an important role in the dynamic airfreight industries worldwide, as the key-enabling factor that makes operations systems, processes, and overall enterprises more agile and productive. It is important that researchers and practitioners working in areas related to this field address the ramifications of advances in both established and emerging information technologies and their impact on airfreight system development and operations. This is due to the fact that accurate information flows among the links of an organisation in a timely, coordinated fashion not only minimizes distortions but also help prevent errors in critical business processes, which tend to result in costly failures in the short run that may undermine viability in the long run. Hence, information systems must be capable of incorporating latest information of events affecting the air-cargo chain, especially in freight capacity management to prevent costly off-loading errors and at the same time permitting the business organisation to benefit from airline rebates.